2021
DOI: 10.1002/joc.7244
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation projections over the Indus River Basin of Pakistan for the 21st century using a statistical downscaling framework

Abstract: We estimate future changes in precipitation over the entire Indus basin of Pakistan with a particular focus on the high-elevation Upper Indus Basin (UIB). A statistical downscaling approach is used. We consider the spatial variability of observed precipitation on seasonal scales. Large-scale atmospheric patterns are employed for general circulation model (GCM) selection and subsequent projections. First, we identify the precipitation governing predictors from ERA-Interim reanalysis. We further quantify the rob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 82 publications
3
1
0
Order By: Relevance
“…The supplementary literature shows a spatial correlation coefficient 0.69, indicating reasonable accuracy [29]. As a result, the findings strengthen their credibility and align with other studies that have reported high performance of CMIP6 models across various geographical settings [30]. Further bolstering the credibility of the findings is consistency across models.…”
Section: Model Evaluation and Historical Analysissupporting
confidence: 84%
“…The supplementary literature shows a spatial correlation coefficient 0.69, indicating reasonable accuracy [29]. As a result, the findings strengthen their credibility and align with other studies that have reported high performance of CMIP6 models across various geographical settings [30]. Further bolstering the credibility of the findings is consistency across models.…”
Section: Model Evaluation and Historical Analysissupporting
confidence: 84%
“…The supplementary literature shows a spatial correlation coefficient of 0.69, indicating reasonable accuracy values [32]. As a result, the findings strengthen their credibility and align with other studies that report the good performance of CMIP6 models across various geographical settings [33]. Further bolstering the credibility of the findings is the consistency across models.…”
Section: Model Evaluation and Historical Analysissupporting
confidence: 84%
“…Both Tmax and Tmin will increase while Tmin will rise more than the Tmax. Previous studies report similar results for the study area and other parts of the world [16,[58][59][60][61]. Rising future temperatures will increase agricultural water demand due to an increase in evapotranspiration [62][63][64].…”
Section: Climate Change Projectionssupporting
confidence: 69%